24-hour rhythm in gene expression of redox pathway enzymes in rat hypothalamus : effect of melatonin treatment - Jiménez Ortega, Vanesa (2009)
Fil: Jiménez Ortega, Vanesa. Universidad Complutense. Facultad de Medicina. Departamento de Bioquímica y Biología Molecular III; España